Green Sister City Cooperation of Surabaya and Kitakyushu: Beyond Ceremonial Paradiplomacy - Utomo, Ario Bimo; Widiana, Fany (Thammasat Review, 2024)
Today, diplomacy is not only carried out by the state. Subnational entities such as cities are also becoming new global political actors, which is no longer an unusual occurrence in the early twenty-first century. In international relations, diplomacy conducted by subnational governments is referred to as parallel diplomacy or paradiplomacy. As a study, paradiplomacy emerged from case studies of federal states and established democracies in Western Europe and North America. Now, paradiplomacy has also begun to be normalised and has become a practice in many countries worldwide. However, the practice of paradiplomacy in developing Asian countries has been criticised for its lack of substance and consequence, and its tendency to be merely ceremonial in nature. This article provides a case study of "green sister city" paradiplomacy conducted between Surabaya and Kitakyushu to illustrate a well-institutionalised paradiplomatic activity built upon real needs. From there, this article attempts to demonstrate defining key factors in creating a functioning paradiplomatic activity: a well-defined motive, a regulating body, and inclusive programs reaching key stakeholders.